Pengaruh Pengomposan Pelepah Eks Panen dan Tunasan pada Rorak Berjarak Satu Meter terhadap Pembungaan Tanaman Kelapa Sawit Menghasilkan Tahun Ke-5 - Ratih Rahhutami; Toto Suryanto (Politeknik Kelapa Sawit Citra Widya Edukasi, 2018)
This research purpose to obtain alternative method to increase flowering of palm oil during the cropping period, to determine the effect of midrib in the rorak towards flowering of palm oil, and to obtain the right number of midribs for composting in rorak. The research was conducted at Teaching Farm of Politeknik Kelapa Sawit Citra Widya Edukasi, Bekasi on October, 2016 to June, 2017. While laboratory analysis included analysis of soil, midrib, and urea fertilizer carried out in the Laboratory of the Department of Soil Science and Land Resources Faculty of Agriculture, Bogor Agricultural University (IPB). The design used was a single-factor completely randomized design (CRD). There were five treatments tested: control (without rorak) (A0), 30 wet midribs + 1 kg urea (A1), 40 wet midribs + 1 kg urea (A2), 30 dry midribs + 1 kg urea (A3), and 40 dry midrib + 1 kg urea (A4). Each treatment was repeated twice and each replication consisted of two plant samples so that there were 20 units of experiment units. Data analysis used was ANOVA Test and BNT Advanced Test at the level of 5%. The results showed that the provision of oil palm midrib compost in rorak could be used as an alternative fertilizer in palm oil plantation, giving palm oil midrib compost in rorak significantly affected the number of oil palm male flowers at 3, 4 and 5 MAA. Whereas for the number of female flowers significantly affected only at 5 MAA, and the number of effective midribs to be used as compost seen from the morphological and physiological responses was 40 dry midribs + 1 kg urea (A4).